Edukasi Penciptaan Layanan Ramah Petugas Satpol PP Untuk Membangun Disiplin Protokol Kesehatan Masyarakat - Prasidi, Abi; Haris, Haris; Salehati, Nurun Ala (Institut Transportasi dan Logistik Trisakti, 2024)
The low discipline of some individuals in implementing health protocols during the pandemic has become a challenging task for the Civil Service Police Unit (Satpol PP). The indifferent and unconcerned attitude in heeding health protocols makes the enforcement process not conducive and has implications for officers' low level of patience. This community service activity aims to provide education on friendly service as a solution to changing the behavior of some Satpol PP officers who are unfriendly into a friendly unit in the eyes of the public. The activity was implemented at the DKI Pemda office, located in Petogogan, Kebayoran Baru District, South Jakarta, involving twenty members, all male. The educational method was implemented in two ways: material presentation and direct field practice. The results of this education can change the mindset of regional apparatuses who are considered arrogant to officers who have a spirit of service to the community. This activity can be a reference to continue from friendly service to excellent service.